Macro-economic Variables and Bank Performance in Nigeria: Fourth Republic Perspective - Ogunlokun, Ayodele Damilola; Adebisi, Adebola Olubunmi (Acta Universitatis Danubius. Œconomica, 2023)
The vagaries of the macro-economic variables make business environment unpredictable and this often portends mammoth implications for various businesses, especially, a critical business such as banking, which the successive governments within the fourth Republic have strived to jealously protect. Therefore, in this study, the impact of macroeconomic factors on the performance of Nigerian banks from 1999 to 2021 was assessed. Data for the study's time period came from the World Bank reports as well as the Statistical Bulletins of the CBN and SEC. To evaluate the data, an ARDL (Autoregressive Distributed Lag) model was employed. Findings showed that, in the long run, lending interest rates had a negative and statistically insignificant impact on the performance of Nigerian banks with a coefficient of -0.0422 (p-value = 0.3860 > 0.05), in contrast to the unemployment rate, which had a negative but statistically significant impact with a coefficient of -0.0534 (p-value = 0.0012 > 0.05); furthermore, gross domestic savings in Nigeria maintained positive and strong relationship with banks performance in the long run with coefficient 0.7970 (p-value=0.0002<0.05). Moreover, finding showed that GDP Per capital income insignificantly stimulated the performance of the banks with coefficient 0.3038 (p-value=0.0963>0.05) while exchange rate was found to be positively and significantly associated with the performance of the banks with coefficient 0.8073 (p-value=0.0334<0.05). In addition, the variables converged in the long run at a speed of 151% with a statistically significant p-value =0.0034<0.05; the Heteroscedasticity test and the Autocorrelation test respectively revealed that the model residuals were Homoscedastic and uncorrelated. Sequel to these findings, the study concluded that while lending interest rate and unemployment rate impeded banks’ performance, gross domestic savings, GDP per capital income and exchange rate facilitated banks’ performance in Nigeria. Accordingly, it was suggested that government should create jobs via industrialization that is matched with locally available inputs, especially in the areas of agriculture so as to firmly address the galloping unemployment rate that is impeding banks performance in the fourth Republic of Nigeria.